PENGARUH DOSIS DAN WAKTU APLIKASI JAMUR MIKORIZA ARBUSKULAR TERHADAP PERTUMBUHAN BIBIT TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq) DI PRE-NURSERY - Putra Ardiansyah (Unit Penelitian dan Pengabdian Masyarakat (UP2M) Politeknik Banjarnegara, 2022)
This study aims to determine the effect of administering Arbuscular Mycorrhizal Fungus (AMF) with different application times on the growth of oil palm seedlings in Pre-Nursery. The sprouts used came from PPKS with the D X P Marihat variety. This research was conducted at the Green House Polytechnic LPP Yogyakarta arranged in a factorial Randomized Block Design (RBD). The first factor was the administration of AMF with the dose used, namely M0 for no AMF, M1 with 5 grams of JMA, and M2 with 10 grams of AMF. The second factor was the time of application which consisted of 3 levels, namely: W1 (Application 5 days before planting), W2 (Application 15 days after planting), and W3 (Application 30 days after planting). From these two factors, 9 treatment combinations were obtained which were repeated 3 times, so that they consisted of 27 experimental units. The treatments were planted in polybags measuring 20 X 20 cm. Each experimental unit consisted of 2 plants, so a total of 54 oil palm seeds were needed. The variables observed were plant height, stem diameter, number of leaves, plant wet weight, and plant dry weight. Analysis of the data using variance (ANOVA) with a significant 5%, if there is a significant difference followed by Duncan's further test (DMRT). The results showed that there was no real interaction between the administration of AMFand the different application times on the observed growth variables. The AMF treatment had no significant effect on plant height, several leaves, wet weight, or dry weight but had a significant effect on stem diameter. Different times of application of AMF did not significantly affect all observed variables, namely plant height, number of leaves, stem diameter, plant wet weight, and plant dryweight.